State constitution as adopted by the Constitutional Convention, Aug. 12, 1865 : To be submitted to the people of Colorado for adoption or rejection, on the first Tuesday of September, 1865 ([publisher not identified], 1865)
The State Constitution as adopted by the Constitutional Convention on August 12, 1865, which was submitted to the public for adoption or rejection in September 1865. Of note, although it was ratified and passed by the United States Congress, it was vetoed by President Andrew Johnson. Colorado did not become a state until 1876.